Age-Dependent Protein Aggregation Initiates Amyloid-β Aggregation - Groh, Nicole; Bühler, Anika; Huang, Chaolie; Li, Ka Wan; van Nierop, Pim; Smit, August B.; Fändrich, Marcus; Baumann, Frank; David, Della C. (Frontiers in Aging Neuroscience, 2017)
Aging is the most important risk factor for neurodegenerative diseases associated with pathological protein aggregation such as Alzheimer’s disease. Although aging is an important player, it remains unknown which molecular changes are relevant for disease initiation. Recently it has become apparent that widespread protein aggregation is a common feature of aging. Indeed, several studies demonstrate that hundreds of proteins become highly insoluble with age, in the absence of obvious disease processes. Yet it remains unclear how these misfolded proteins aggregating with age affect neurodegenerative diseases. Importantly, several of these aggregation-prone proteins are found as minor components in disease-associated hallmark aggregates such as amyloid-β plaques or neurofibrillary tangles. This co-localization raises the possibility that age-dependent protein aggregation directly contributes to pathological aggregation. Here, we show for the first time that highly insoluble proteins from aged C. elegans or aged mouse brains, but not from young individuals, can initiate amyloid-β aggregation in vitro. We tested the seeding potential at four different ages across the adult lifespan of C. elegans. Significantly, protein aggregates formed during the early stages of aging did not act as seeds for Aβ aggregation. Instead, we found that changes in protein aggregation occurring during middle-age initiated Aβ aggregation. Mass spectrometry analysis revealed several late-aggregating proteins that were previously identified as minor components of amyloid-β plaques and neurofibrillary tangles such as 14-3-3, Ubiquitin-like modifier-activating enzyme 1 and Lamin A/C, highlighting these as strong candidates for cross-seeding. Overall, we demonstrate that widespread protein misfolding and aggregation with age could be critical for the initiation of pathogenesis, and thus should be targeted by therapeutic strategies to alleviate neurodegenerative diseases.